Interdisciplinary Trust Meta-Analysis. Analysis of High Rank Trust Articles between 1966 and 2006 - Tara Ebert (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2007)
A meta-analysis of approximately 800 trust articles written from 1966 to 2006 in A+, A, and B journals are structured and analyzed. Contributions from the number of published trust articles, multidisciplinarity, trust objects, trust interactions types, and occurrence of key variables – in addition to the term trust - are deduced.
urn:nbn:de:bvb:19-epub-1388-9
Keywords: A30; 650; trust